Spatial Coverage Mapping Of Community Health Centers Using Geographic Information Systems: Pemetaan Cakupan Spasial Pusat Kesehatan Masyarakat Menggunakan Sistem Informasi Geografis - Marisa Marisa; Apri Yulda; Febri Ramanda; Sidik Praptomo; Yessy Fitriani (Universitas Muhammadiyah Sidoarjo, 2026)
General Background The uneven territorial distribution of primary care facilities creates structural barriers to equitable public access. Specific Background Bungo Regency faces geographical challenges across its vast territory of 4,769.60 km², resulting in unequal accessibility to its 19 medical facilities. Knowledge Gap While prior research explored mobile-based applications, a systematic geographical evaluation using standardized analytical methods remains absent for this region. Aims This study evaluates the geographical reach of 19 medical facilities across 17 sub-districts utilizing QGIS software to plan equitable service distribution. Results Applying a uniform 5 km radius, findings reveal that only 25.2% of the total regency area falls within the service range. Among the 17 sub-districts, three are fully reached, and fourteen are partially reached, with Limbur Lubuk Mengkuang and Bathin III Ulu recording the lowest accessibility at 9.0% and 10.9%, respectively. Novelty The research utilizes a homogeneous comparative Euclidean distance approach without urban-rural classification to uncover precise regional distribution disparities. Implications These findings provide foundational evidence for urgent policy interventions, specifically the development of auxiliary posts and mobile programs in critically underserved sub-districts to achieve regional equity. Highlights • QGIS software evaluation reveals that a standardized service radius reaches only a quarter of the total regency territory. • Fourteen sub-districts face partial service deficits, with specific regions experiencing critically low accessibility levels below eleven percent. • The identified regional disparities necessitate targeted infrastructure developments like auxiliary posts to achieve equitable primary care distribution. Keywords Geographic Information Systems; Community Health Centers; Spatial Coverage; Buffer Analysis; Healthcare Accessibility